Silent Struggles: Sexual Violence Experiences of SGM Youth in Rural Vhembe District, Limpopo, South Africa - Ramavhoya, Vhulenda; Ikhile , Ikekhwa Albert; Mavhandu-Mudzusi , Azwihangwisi Helen (Journal of Ecohumanism, 2025)
Introduction: This paper focuses on sexual violence perpetrated against SGM youth globally, and especially at coming out age. This research aims at establishing the history of Sexual Violence among SGM youths in the rural Vhembe District, Limpopo Province, South Africa. Method: This research was a qualitative interpretative phenomenological study of young sexual and gender minorities between the ages of 18 and 35 with experiences of sexual violence. Ten participants were purposively sampled based on the criterion and interviewed in an unstructured manner. Illustratively, data were reviewed through the lens of interpretative phenomenological analysis with themes emerging from the data themselves. Findings: Four predominant themes were identified: sexual violence, the effects of sexual violence, support, and coping strategies. A range of the sexual violence cases revealed by the study took place in the context of homes, workplaces, and even prisons showing that it is rife in rural areas. Conclusion: The paper makes suggestions for preventing, responding to, and handling the impact and aftermath of sexual violence specifically targeting SGM persons, with a focus on strengthening nursing care for these survivors. These insights will hopefully help in moving towards fair distribution of health and well-being, improve the quality of care for all patients, and work toward patients, especially SGM youth, in rural South Africa being treated with dignity and properly cared for where they seem to be most at risk.